Formation mechanism and sustainable productivity impacts of non‐grain croplands: Evidence from Sichuan Province, China. (27th December 2022) - Liang, Xinyuan; Jin, Xiaobin; Liu, Jing; Yin, Yanxing; Gu, Zhengming; Zhang, Junyi; Zhou, Yinkang
Abstract: Non‐grain cropland is a typical phenomenon with some common characteristics globally. As the most populous country, China's non‐grain cropland threatens global food supply stability and affects food production sustainability under the current complex situation of international food security. This paper used Sichuan Province, China, to explore the formation mechanism of non‐grain cropland and its potential impact on sustainable productivity, given the regional environment complexity and socioeconomic representativeness. High‐precision land survey data were used to detect multiscale non‐grain influencing factors and discuss non‐grain impacts on soil state to fill the knowledge gap on microlevel development of non‐grain issues. Results show that rotation type is the region's most abundant and widely distributed cropland type, accounting for about 59.38% of the total cropland area; the second is abandonment type. Urbanization indicators are the common factors affecting the non‐grain spatial distribution on the global scale; environmental variables' impact on non‐grain shows significant differences in geographical locations on the local scale. Overall, cash type and intercrop type aim at improving production conditions. Rotation type and fallow type mostly occur in areas with low production capacity and are prominently driven by policies. Abandonment type is subject to terrain constraints, production conditions, and social economy. Additionally, non‐grain trends have not caused significant damage to soil sustainable productivity except for the positive promotion of field biodiversity. Non‐grain cropland can be divided into three clusters according to the corresponding average soil fertility state, rotation, intercrop, cash, abandonment, and fallow. Policymakers must implement specific policies for different cropland types and formulate more refined farming management plans.